2011
DOI: 10.1159/000330803
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Interleukin-1 Receptor Accessory Protein b to Interleukin-1 Actions in Neuronal Cells

Abstract: Interleukin (IL)-1 is an important neuroimmunomodulator and a key mediator of inflammation during brain disorders. It acts on neuronal and glial cells via binding to the IL-1 type 1 receptor and IL-1 receptor accessory protein (IL-1RAcP). More recently, a neuronal-specific isoform of IL-1RAcP, named IL-1RAcPb, has been identified. Our aim was to determine the role of IL-1RAcPb in IL-1 actions in neuronal and glial cells, and to further explore the signaling mechanisms of IL-1 in neurons. We found that IL-1RAcP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Experiments in mice knocked‐out for IL‐1R3b show that this alternative receptor is important for neuroprotection in brain inflammation, whereas it has no involvement in the peripheral effects of IL‐1 . IL‐1R3b KO neurons cannot respond to IL‐1α by inducing phosphorylation of p38 . In agreement with this finding, it was also shown that IL‐1β could induce phosphorylation of p38 and Src, as well as potentiation of NMDA‐induced influx of calcium, in an IL‐1R3b‐dependent manner in neurons .…”
Section: Focus On the Il‐1r Familymentioning
confidence: 53%
See 2 more Smart Citations
“…Experiments in mice knocked‐out for IL‐1R3b show that this alternative receptor is important for neuroprotection in brain inflammation, whereas it has no involvement in the peripheral effects of IL‐1 . IL‐1R3b KO neurons cannot respond to IL‐1α by inducing phosphorylation of p38 . In agreement with this finding, it was also shown that IL‐1β could induce phosphorylation of p38 and Src, as well as potentiation of NMDA‐induced influx of calcium, in an IL‐1R3b‐dependent manner in neurons .…”
Section: Focus On the Il‐1r Familymentioning
confidence: 53%
“…The result is a membrane form of IL‐1R3 with an anomalous TIR domain in which the αD helix is disrupted and much longer intracellular tail . IL‐1R3b is exclusively present in the brain, mostly in neurons, but not in microglia or astrocytes . It has been shown that IL‐1R3b can form a complex with IL‐1R1 bound to IL‐1, although there are no univocal data of the downstream signaling initiated by this receptor complex .…”
Section: Focus On the Il‐1r Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Primary neuronal cell cultures were prepared from the brains of mouse embryos at 14 to 16 days of gestation as described previously [17]. Cells were seeded at a density of 6 x 10 5 cells/ml onto poly-D-lysine (PDL)-coated tissue culture plates in neurobasal medium containing 1 U/ml penicillin, 1 μg/ml streptomycin, 1% glutamine, 5% PDS, 2% B27 without antioxidants and 20 μM 5’-fluoro-2-deoxyuridine (FUDR) to inhibit glial cell growth.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, AcPb expression is restricted to neurons. Though both proteins modulate MAP kinases activity and in particular the p38 pathway, AcPb, unlike AcP, does not activate canonical NF-κB transcription factors (Huang et al, 2011; Nguyen et al, 2011). Consequently, AcPb signaling has relatively marginal effects of gene transcription compared to AcP.…”
Section: Introductionmentioning
confidence: 99%